The Effect Of The Role Of Internal Audit Units On The Performance Of Insurance Claim Services And Management Systems With Fraud Prevention As Intervening Variables In Tarumajaya Hospital, Bekasi - Cut Eva Safitri; Fresly Hutapea; Yanuar Ramadhan (Jurnal Health Sains, 2022)
Technological developments have an impact on making it easier for fraud to occur which has an impact on service performance. Good service performance is the achievement of an unqualified opinion on the hospital management audit. The purpose of this study was to analyze the effect of the role of the internal audit unit on service performance and insurance claims management system with fraud prevention as an intervening variable at Tarumajaya Hospital, Bekasi. The research method used is explanatory causality quantitative analysis with quantitative methods. With a sample of 40 people. The data were analyzed by path analysis through SEM-PLS. The results of the analysis and discussion show that there is a direct and indirect influence on the role of the internal audit unit on service performance and the insurance claim management system with fraud prevention as an intervening variable at Tarumajaya Hospital. internal examination unit on service performance and insurance claim management system at Tarumajaya Hospital, Bekasi. In addition, there is an influence of the role of the internal audit unit on fraud prevention, service performance and insurance claims management system at Tarumajaya Hospital, Bekasi. The research implication shows that optimal service can be achieved if it has optimal service performance.